Effect of stress management training on depression, stress and coping strategies in pregnant women: a randomised controlled trial - Sukran Ertekin Pinar; Ozlem Duran Aksoy; Gulseren Daglar; Z. Burcu Yurtsal; Busra Cesur (Taylor & Francis Group, 2018)
Introduction: Pregnancy is a period of important biological and psychosocial changes and a period that carries high risk of experiencing anxiety and stress. It is important to reduce the depression and stress that is experienced in this period or to reduce the severity of the stress and to increase the stress coping power of the pregnant women. The research was conducted to examine the effect of stress management training on pregnant women's depression, stress and methods for coping with stress. Methods: Randomised controlled study of 202 pregnant women (experimental group: 103; control group: 99). The experimental group received stress management training and standard care; the control group received standard care. Data were collected using a Personal Information Form, the Beck Depression Inventory (BDI), Perceived Stress Scale (PSS) and ways of coping inventory (WCI). Results: Both groups showed a decrease in average BDI score during the study; the decrease was greater in the experimental group (p < 0.05). In the two assessments carried out after training the experimental group had lower average PSS scores than the control group (p < 0.05). At the second and third assessments the experimental group had higher scores than the control group on the self-confident approach and search for social support approach WCI subscales (ps < 0.05). Discussion: The average BDI and PSS scores of pregnant women in the experimental group decreased after training in coping with stress. Their scores on the self-confident approach, optimistic approach and search for social support WCI subscales increased. Stress management training is an effective method of encouraging pregnant women to take a positive approach to coping with stress.